Sustainable Urbanism through service in Littleton, Colorado - Burnham, Kent D. (Kansas State University, 2009)
Once a standalone town on the periphery of Denver, Littleton is now completely surrounded by other cities on all sides. Much of northeast Littleton is experiencing many of social and demographic issues associated with an aging suburb. Buildings are showing signs of age and neglect and the area has higher incidences of crime, gang activity, drugs, and graffiti than the rest of Littleton. Because it cannot expand outward, the City of Littleton must look at ways to redevelop within its city limits. This study focuses on achieving service in an infill development in northeast Littleton, Colorado. Research about the urban design was conducted and case studies of were documented. A program was written based on the research and a thorough inventory and analysis of existing site conditions. Based on the program, structures and site elements were located in northeast Littleton based on the principles of Sustainable Urbanism. The design achieves service through the Sustainable Urbanist principles of defined center and edge, compactness, completeness, connectedness, and biophilia. Because the design is focused on achieving service, not strictly on the placement of buildings within an urban framework according to a design style, the result is a community that is able to support local business and mass transit through walkability, increased density, and outside connection.
Keywords: Sustainable Urbanism; Service; Littleton; Colorado; Landscape Architecture (0390)